(اﻟﺟودة اﻟﺷﺎﻣﻠﺔ ﻓﻲ اﻟﺗﻌﻠﯾم ﻣﻔﮭوﻣﮭﺎ ، ﻣراﺣﻠﮭﺎ ، روادھﺎ ، ﻣﺣﺎورھﺎ (ﺑﺣث ﻣﺳﺗل ﻣن اطروﺣﺔ دﻛﺗوراه (Journal of the College of Education for Women, 2019)
The principle of total quality not the result of the modern era, but has its roots entrenched in the foot, the king announced the Babylonian (Hammurabi) before five thousand years: The person who builds a house fall to the occupants, Fiktlhm; the sentence penalty, from here, established Babylonian civilization oldest concerns quality and perfection in the work, although the roots of quality stretch in the ancient Pharaonic civilization represented by the pyramids and temples, and in the Chinese civilization in the Great Wall of China. The concept of quality is present in all the teachings of Islam Bamadaminh all, which represents the value of an Islamic urged the Qur'an to the total quality in all the work which is supposed to be performed by human and understand that by saying the Almighty: "It is not righteousness that they turn away your faces before the East and Morocco, but the road from a safe God and the Last Day and the angels and the Book and the Prophets, and brought money for the love of kin and the orphans, the needy and the wayfarer and the questioners in the necks and established prayer, he came to Zakat and Movon Bahdhm if the covenant and steadfast in Alboads and in adversity, when valor of those who believe and those are the righteous "(al-Baqarah, verse: 177). This research has focused on the concept of quality according to the following themes: History, and the concept of total quality in Islam, and the stages of evolution of the concept of quality, and terms of quality, the most prominent pioneers of quality, axes of the overall quality of university education, and curriculum and overall quality. He then discussed how the researcher turned the concept of quality from industry to education, and the concept of total quality in education in general and in higher education in particular.